Case Study of Rock Debris Avalanche Gravel Liquefied During 1993 Hokkaido-Nansei-Oki Earthquake - Kokusho, Takeji; Tanaka, Yukihisa; Kawai, Tadashi; Kudo, Kouji; Suzuki, Kouichi; Tohda, Shinji; Abe, Shintaro (SOILS AND FOUNDATIONS, 1995)
During the Hokkaido-Nansei-Oki Earthquake, a high-land area around the foot of the volcano, Mt. Komagatake, in Hokkaido in Northern Japan experienced liquefaction inflicting damage caused by differential settlement in more than forty houses in the area. Several geotechnical site investigations were carried out to study the cause of the damage at a typical liquefaction site. Initial surveys including trenching disclosed that Holocene rock debris avalanche deposit originated from the volcano with 70 to 80% of gravel content located immediately underneath one damaged house actually liquefied and settled. By means of bore-hole drilling, penetration testing and geophysical exploration, the cross-sectional profile of the rock avalanche gravel layer was identified. The shear wave velocity of the upper part of the layer was found to be unexpectedly lower than 100 m/s. In order to quantitatively evaluate the liquefaction potential of the gravel layer, an undrained cyclic triaxial test was performed on large intact samples obtained using the in-situ freezing sampling. The stress ratio measured in the test was lower than the seismic induced stress ratio estimated from maximum surface accelerations in nearby earthquake recording sites, justifying the earthquake-induced liquefaction. In comparison with previously investigated properties of Pleistocene gravels, low values in relative density, shear-wave velocity and penetration resistance of this gravel have been highlighted, indicating a rather unique environment in forming the rock debris avalanche layer.